Motivating employees: Beyond the carrot-and-stick techniques (2019)
This article responds to three main objectives: First, it challenges the widespread use of tangible rewards (bonuses, prizes, gifts) or punishments to motivate employees and makes reference to various studies which demonstrate that such incentives do not promote intrinsic motivation and may even decrease existing motivation. Second, it presents Self-determination Theory as an alternative model to motivate people in different environments. This model defines motivation in terms of volition or autonomy and identifies three basic psychological human needs: autonomy, competence, and relatedness. Several empirical studies, reported in the article, demonstrate that the satisfaction of these needs are directly related to intrinsic motivation and, therefore, with greater job satisfaction and productivity. Finally, three motivational strategies are offered to help institutional leaders satisfy their employees’ basic psychological needs.